If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 0.25x = 0.8 + -5 Combine like terms: 0.8 + -5 = -4.2 6 + 0.25x = -4.2 Solving 6 + 0.25x = -4.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 0.25x = -4.2 + -6 Combine like terms: 6 + -6 = 0 0 + 0.25x = -4.2 + -6 0.25x = -4.2 + -6 Combine like terms: -4.2 + -6 = -10.2 0.25x = -10.2 Divide each side by '0.25'. x = -40.8 Simplifying x = -40.8
| X+0.3x=60 | | 4-7=3x+1 | | 6x-9x=1-7 | | X^2/2-5x-17 | | x^2+4x-16=-4 | | 5-(2x-1)=12-x | | 6/2x(3-4x)=2/3 | | 6y-1=7 | | 72pq/16q | | (3)^(-2)/(-2)^(-3) | | 1.6=-16x^2+64x | | -56x^2+14x+42=0 | | (5x^2-6x^4)+(7x^2+3x^4)=0 | | log[6](4x+5)=3 | | 21x^2+10x=0 | | 2+7k=65 | | 2x-12=-26 | | -5(p-2)+3p=6(p-4) | | R^2+16r-76=0 | | 6x2-12x-48/3x2-12x-36 | | 11p^2=-1 | | 4(7x-10)=18 | | x^5-6x^2+3x+3=0 | | y^2-3ay+2a^2=0 | | g(2)=4t^2-5t+3 | | (12a^3bc-^4/-4ab^5c^2)^3 | | -24x+4y=12 | | 14p^2-59p+35=0 | | g(t-2)=4t^2-5t+3 | | 2.5x-25=12 | | 2.5x-15=12 | | 5a-11=8a+8+14a+1 |